2017
DOI: 10.1111/sjoe.12214
|View full text |Cite
|
Sign up to set email alerts
|

Do Government Purchases Affect Unemployment?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…It also includes a discussion regarding data comparability, owing to the country-specific nature of the policy intervention variables and the change in the OECD classification system on policy interventions in 2002. 15 A variety of econometric estimators, technical fixes and diagnostic tests exist today to treat the endogeneity issue, which have been successfully used in economic empirical analyses (Halla et al 2016;Overesch and Rincke 2011), including those studying labour market policies and institutions (Holden and Sparrman 2017;Hijzen and Martin 2013). 16 The model was also tested for heteroskedasticity using the robust option available.…”
Section: Endnotesmentioning
confidence: 99%
“…It also includes a discussion regarding data comparability, owing to the country-specific nature of the policy intervention variables and the change in the OECD classification system on policy interventions in 2002. 15 A variety of econometric estimators, technical fixes and diagnostic tests exist today to treat the endogeneity issue, which have been successfully used in economic empirical analyses (Halla et al 2016;Overesch and Rincke 2011), including those studying labour market policies and institutions (Holden and Sparrman 2017;Hijzen and Martin 2013). 16 The model was also tested for heteroskedasticity using the robust option available.…”
Section: Endnotesmentioning
confidence: 99%
“…According to empirical evidences of [8,9,10,11] government expenditure can enhance the level of employment and reduce unemployment in both developed and developing countries. However in spite of the huge government expenditure being spent on productive sectors such as infrastructures, defense of the citizenry, education and healthcare in Africa, there has been continuous rise in the level of unemployment in the continent.…”
Section: Background To the Studymentioning
confidence: 99%
“…Holden and Sparrman [9] empirically analyzed the effect of government purchases on unemployment in 20 OECD countries from 1980 to 2007. Using ex post factor methodology, the findings revealed that an increase in government purchases reduced unemployment by about 0.3 percentage point in the same year.…”
Section: Studies On the Relationship Between Unemployment And Governmmentioning
confidence: 99%
“…Some studies observed that government intervention crowds‐in private investment, alluding to complete interventionist role by government (Cardoso, ). Specifically, Holden and Sparrman (), using 20 OECD countries data from 1980–2007, observed that increases in government purchases leads to decline in unemployment. Lugo () sums that government expenditure crowds‐out private investment when: (1) government invests in inefficient state‐owned firms; (2) private investors expect higher taxes to finance increases in expenditures in the future; and/or (3) the public sector competes with private sector for domestic credit.…”
Section: Review Of Related Literaturementioning
confidence: 99%